The effectiveness of two different at-home tooth whitening products as evaluated by Dino-lite digital microscope - Mohamad, Muhammad Afif Naufal; Mohd Nasir, Mohamad Nasrul Shahmi; Hassan, Haszelini; Mohd. Nor, Hikmah; Ko, Bo Bo (Kulliyyah of Dentistry, International Islamic University Malaysia (IIUM), 2022)
Many desires brighter and whiter teeth in a quicker and easier way but in less expensive way. Therefore, over-the-counter tooth whitening solutions such as toothpaste, mouth rinses, gel, varnish paints, and strips are regarded a good option, albeit their efficiency is questioned. Different types of oxidizing agents such as hydrogen peroxide and carbamide peroxide used in the tooth whitening products as bleaching agents may produce different degree of shade change. Thus, this study aimed to evaluate the effectiveness of two different at-home tooth whitening products related to the changes in tooth shade and enamel surface appearance. Twenty-one samples of extracted human teeth were used in this study. The samples were divided into seven groups and were exposed to two at-home tooth whitening products; Beyond Care (6% hydrogen peroxide) and White Smile (16% carbamide peroxide) according to the recommended guidelines and exceeded the recommended guideline by 3 times and 5 times for each whitening product for 14 consecutive days. Photos of enamel surface appearance and tooth shades of samples were taken using Dino-Lite Digital Microscope and DSLR camera at pre- and post-treatment. Comparison was made using Ivoclar Vivadent shade guide. The results revealed that six samples that were exposed to Beyond Core White (CW) in the respective exposure time showed changes in shade. Meanwhile, only two samples treated with White Smile (WC) showed changes after being exposed to five times the recommended guideline. However, no significant surface change in enamel was observed. Samples with mild fluorosis had shown improvement after being exposed to five times the recommended guidelines for both agents. In conclusion, no shade changes were observed in all samples that were tested using the recommended guidelines. The whitening efficacy of Beyond Core White was found to be superior to White Smile at three and five times the recommended guidelines.